The Effect of Customer Experience and Video Marketing on Satisfaction Levels and Word-of-Mouth on TikTok in West Java - Sudirjo, Frans; Setiyawan, Heri; Nurhasanah, Dila Padila (Westscience Press, 2025)
This study investigates the effect of customer experience and video marketing on satisfaction levels and word-of-mouth in the context of TikTok usage in West Java, Indonesia. Utilizing a quantitative approach, data were collected from 230 TikTok users through a structured questionnaire employing a Likert scale (1-5). The analysis, conducted using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3), reveals that customer experience and video marketing significantly influence satisfaction levels and word-of-mouth. Customer experience emerges as the more influential factor in shaping user satisfaction and advocacy. These findings underscore the importance of optimizing both user experience and marketing strategies to enhance consumer engagement and loyalty. This study contributes to the growing body of literature on digital marketing and consumer behavior, offering actionable insights for businesses aiming to succeed on social media platforms.